Study on preference and willingness to pay for urban marathon event experience from an embodied perspective - Cuixia Yi; Zhipeng Liu; Tao Yang; Kaidi Zhang (PLoS ONE, 2025)
Urban marathons have become important platforms for fulfilling individuals’ aspirations for a better life and promote residents’ health. This study employs a choice experiment method and utilizes embodied theory to explore attributes and design attributes levels of urban marathon products, based on an analysis of social network text content. Through a questionnaire survey of marathon participants, the results reveal that prioritize embodied experiential attributes in the following order: visual experience, auditory experience, extended recollection, self-transcendence, kinesthetic experience, registration fees, and social bonding. Runners with higher incomes and event expenditure prefer visual experiences, while those who participating more frequently exhibit lower preferences for kinesthetic experience. Runners with higher education levels prioritize off-scene experiences. Based on preference heterogeneity, four distinct runner types are identified: ritual-driven runners, audio-visual experience-oriented, achievement-oriented, and social emotion-oriented. Management implications and recommendations for organizers of urban marathon events are provided.